Desempenho agronômico de cultivares de figueira visando à produção de figos verdes em regiões de clima subtropical - Figueiredo, Alana Lauar (2017)
The fig tree (Ficus carica L.) belongs to the family Moraceae, in which predominate plants with arboreal and shrub growth. Only the 'Roxo de Valinhos' cultivar has great commercial expression, due to the rusticity, vigor and productivity, in relation to the other cultivars. Some diseases such as fig rust severely attack the „Roxo de Valinhos‟ cultivar that is highly susceptible to the pathogen, making it vulnerable in case of its incidence. Due to this, the objective was to evaluate the productive performance of different fig cultivars as alternatives to the 'Roxo de Valinhos' cultivar, in order to diversify the Brazilian fig crops. The experiment was conducted in the fruit sector of the Department of Agriculture (DAG) of the Federal University of Lavras (UFLA), with eighteen fig tree cultivars: „Bruswick‟, „Mini Figo‟, „Princesa‟, „Troiano‟, „Frucôte‟, „Roxo de Valinhos‟, „Calabacita‟, „Lampa Preta‟, „Colo de Dama‟, „Nazaré‟, „Bêbara Branca‟, „Dauphine‟, „Negro de Bursa‟, „Lemon‟, „Montes‟, „Três num Prato‟, „Pingo de Mel‟ and „Maia‟. The experimental design was a randomized block design with four blocks, two plants per plot and spacing of 1.5m x 3.0m. It was conducted evaluations of agronomic performance (yield, estimated yield, length and diameter of branches, number of fruits per plant and fruit mass), and phenological monitoring of cultivars (beginning and end of harvest, harvesting duration, length and diameter of branches, and number of nodes in the branches). The 'Bruswick' and 'Troiano' cultivars may be alternatives for the diversification of the Brazilian fig crops because they present suitable productive and phenological characteristics for Brazil.